2002
DOI: 10.1530/eje.0.1470181
|View full text |Cite
|
Sign up to set email alerts
|

Meal timing, fasting and glucocorticoids interplay in serum leptin concentrations and diurnal profile

Abstract: Background: In a previous study, we reported a 4-fold increase in serum leptin following total parenteral nutrition given after surgery. We hypothesised that the perioperative fasting and stress contributed to this, possibly mediated by increased serum insulin and cortisol. Objective: To test the hypothesis that fasting, in combination with glucocorticoids, sensitises the leptin response to subsequent energy intake. Design: Healthy volunteers were randomised into two groups, one group received dexamethasone (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 46 publications
(33 reference statements)
3
35
1
Order By: Relevance
“…It has been shown that leptin has a diurnal pattern, which peaks at night (25)(26)(27). Several studies have shown that, during energy restriction, not only fasting leptin concentrations, but also the diurnal variation of these concentrations, is decreased (26,27).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that leptin has a diurnal pattern, which peaks at night (25)(26)(27). Several studies have shown that, during energy restriction, not only fasting leptin concentrations, but also the diurnal variation of these concentrations, is decreased (26,27).…”
Section: Figurementioning
confidence: 99%
“…Several studies have shown that, during energy restriction, not only fasting leptin concentrations, but also the diurnal variation of these concentrations, is decreased (26,27). Additionally, several studies have shown that carbohydrate composition affects the diurnal pattern of leptin.…”
Section: Figurementioning
confidence: 99%
“…Leptin levels in serum show diurnal variations in humans (Sinha et al 1996) and mice (Ahima et al 1998) associated with the dark period and are entrained to mealtime (Elimam & Marcus 2002). The relationship of leptin as a peripheral signal with the main circadian clock, the SCN, was recently explored in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Leptin also demonstrates a diurnal pattern of secretion, and levels rise throughout the day and fall at night. Continued fasting results in a delayed rise in leptin [9,10]. Consequently, women with disordered eating and decreased energy consumption have been shown to have lower leptin levels with both lower baseline levels and a blunted diurnal curve [11,12].…”
Section: Pathophysiology Of Amenorrheamentioning
confidence: 99%